Outcomes and Risk Factors of Patients With COVID-19 and Cancer (ONCORONA): Findings from The Philippine CORONA Study - Espiritu, Adrian I.; Larrazabal, Ramon B.; Sy, Marie Charmaine C.; Villanueva, Emilio Q.; Anlacan, Veeda Michelle M.; Jamora, Roland Dominic G. (Frontiers in Oncology, 2022)
Background A study conducted in China on patients with coronavirus disease 2019 (COVID-19) showed that cancer conferred a five times increased risk for needing intensive care admission and mortality; No data has yet been collected and published from the Philippines. Thus, the investigators conducted this substudy to determine the association of having a history of cancer with clinical outcomes among patients included in the Philippine CORONA Study. Methodology Multi-center, retrospective cohort design Results A total of 244 patients had a history of cancer, out of 10,881 COVID-19 hospital admissions. After adjusting for different confounding variables of interest, having cancer was significantly associated with a 75% increased odds of having severe/critical COVID-19 at nadir (CI 95% 1.32, 2.33; p < 0.001). After adjusting for different confounding variables of interest, having cancer was significantly associated with the following time-to-event outcomes: 72% increase in hazard of in-hospital mortality (CI 95% 1.37, 2.16; p < 0.001), 65% increase in hazard of respiratory failure (CI 95% 1.31, 2.08; p < 0.001), and 57% increase in hazard of being admitted to ICU (CI 95% 1.24, 1.97; p < 0.001). Conclusion A history of cancer conferred poorer clinical outcomes on adult, hospitalized COVID-19 patients.